Strep-tag II Mutant Maltose-binding Protein for Reagentless Fluorescence Sensing - Siti Halimah Hasmon; Goh Kian Mau; Saiful Anuar Karsani; Anthony Cass; Shafinaz Shahir (Tropical Life Sciences Research, 2016)
Maltose-binding protein (MBP) is a periplasmic binding protein found in gram-negative bacteria. MBP is involved in maltose transport and bacterial chemotaxis; it binds to maltose and maltodextrins comprising ?(1-4)-glucosidically linked linear glucose polymers and ?(1-4)-glucosidically linked cyclodextrins. Upon ligand binding, MBP changes its conformation from an open to a closed form. This molecular recognition—transducing a ligand-binding event into a physical one—renders MBP an ideal candidate for biosensor development. Here, we describe the construction of a Strep-tag II mutant MBP for reagentless fluorescence sensing. malE, encoding MBP, was amplified . A cysteine residue was introduced by site-directed mutagenesis to ensure a single label attachment at a specific site with a thiol-specific fluorescent probe. An environmentally sensitive fluorophore (IANBD amide) was covalently attached to the introduced thiol group and analyzed by fluorescence sensing. The tagged mutant MBP (D95C) was purified (molecular size, 42 kDa). The fluorescence measurements of the IANBD-labeled Strep-tag II–D95C in the solution phase showed an appreciable change in fluorescence intensity (dissociation constant, 7.6 ± 1.75 ?M). Our mutant MBP retains maltose-binding activity and is suitable for reagentless fluorescence sensing. Protein pengikat maltosa (MBP) adalah protein pengikat periplasmik yang boleh dijumpai di dalam bakteria gram negatif. MBP terlibat di dalam proses pengangkutan maltosa serta kemotaksis bakteria; ia mengikat pada maltosa serta maltodekstrin yang mempunyai rangkaian linear ?(1-4)-glukosilik polimer glukosa dan rangkaian siklodekstrin ?(1-4)-glukosilik. Semasa protein mengikat pada ligan, perubahan struktur konformasi MBP berlaku dari bentuk terbuka ke bentuk tertutup. Pengecaman molecular ini yang menyebabkan transduksi pengikatan ligan kepada bentuk fizikal menjadikan MBP calon yang sesuai sebagai penderia pendaflour tanpa reagen. Di sini, kami akan menerangkan bagaimana membina mutan Strep-tag II MBP untuk dijadikan sebagai penderia pendaflour tanpa reagen. Gen malE, yang mengekodkan MBP telah diamplifikasikan. Residu sistina telah diperkenalkan melalui proses tapak terarah mutagenesis agar label lekatan tunggal pada tapak yang spesifik yang mempunyai kuar pendaflour spesifik-tiol. Fluorofor yang sensitifpada persekitaran (IANBD amide) terlekat secara kovalen pada kumpulan tiol yang diperkenalkan sebelum ini da kemudian dianalisi secara deria pendaflour. Mutan MBP (D95C) telah ditulenkan (saiz molecular, 42 kDa). Ukuran pendaflour Strep-tag II–D95C yang telah dilabel oleh IANBD di dalam larutan telah menunjukkan perubahan keamatan pendaflour yang memberangsangkan (pemalar penguraian Kd 7.6 ± 1.75 ?M). Mutan MBP berjaya mengekalkan aktiviti pengikatan kepada maltosa dan sesuai dijadikan sebagai penderia pendaflour tanpa reagen.